To find an expression equivalent to 1/4x - 36, you need to distribute the 1/4 to both terms in the parentheses.
The correct expression would be 1/4(x) - 1/4(36).
Simplifying further gives you 1/4x - 9.
Therefore, the correct expression is D) 4x - 9.
Which expression is equivalent to 1/4
x − 36?
Responses
A 1/4 (x + 144)
B 1/4 (x − 144)
C 1/4 (x − 9)
D 4x − 9
5 answers
wrong
Apologies for the incorrect response.
Let's distribute 1/4 to both terms in the expression 1/4x - 36:
1/4 * x = x/4
1/4 * -36 = -36/4 = -9
So, the equivalent expression is x/4 - 9, which can be simplified as 1/4 (x - 36).
Therefore, the correct expression is C) 1/4 (x - 36).
Let's distribute 1/4 to both terms in the expression 1/4x - 36:
1/4 * x = x/4
1/4 * -36 = -36/4 = -9
So, the equivalent expression is x/4 - 9, which can be simplified as 1/4 (x - 36).
Therefore, the correct expression is C) 1/4 (x - 36).
Which expression is equivalent to -1/5(10x + 15) - 2?
Responses
A -2x – 1
B -2x – 4
C -2x – 3
D -2x – 5
Responses
A -2x – 1
B -2x – 4
C -2x – 3
D -2x – 5
To find an equivalent expression to -1/5(10x + 15) - 2, you need to distribute the -1/5 to both terms in the parentheses and then combine like terms.
First, distribute -1/5 to 10x and 15:
-1/5 * 10x = -10/5 * x = -2x
-1/5 * 15 = -15/5 = -3
So, the expression becomes -2x - 3.
Therefore, the correct expression is C) -2x - 3.
First, distribute -1/5 to 10x and 15:
-1/5 * 10x = -10/5 * x = -2x
-1/5 * 15 = -15/5 = -3
So, the expression becomes -2x - 3.
Therefore, the correct expression is C) -2x - 3.